Self-Healing, Digital Activism and Its Continuance on False Consciousness - Bethari, Chili Podhang; Alyanto, Jihan Nurul Savira; Pasopati, Rommel Utungga (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
This article exposes the matter of false consciousness in self-healing as one of contemporary digital activism. Self-healing can be defined as a process in which the body becomes healthy or complete again. The idea itself has been adopted in a wide variety of social media namely Instagram and Tiktok. However, the concept of self-healing itself is shaped by shadow awareness as supported by false consciousness by Gyorgy Lukacs. This article uses qualitative method through explorative approach to understand new points of digital activism. In analysis, self-healing is not actualizing self-awareness, but only to comfort the mind and body from existing busy routines. Self-healing is not matter of amending true self, but as such escapism from busy daily routines. In conclusion, self-healing indeed deteriorates the ultimate idea of healing itself by indicating such false consciousness. It is not real, but plays as a mere illusory shadow